Effect of Debt to Equity and Earning Per Share on Dividend Policy in Property and Real Estate Companies - Erawati Kartika; Mirza Anindya Pangestika; Feny Fidyah; Ummu Kalsum; Edy Susanto (HM Journals, 2023)
This study aims to determine and analyze effect of debt to equity and earning per share on dividend policy in Property and Real Estate Companies. This study uses the design of causal associative research. Population in this study is Property and Real Estate Companies listed on the Indonesia Stock Exchange for the period 2018 to 2022. Sampling technique is taken using a purposive sampling technique. The number of observations in the study is 5 years multiplied by 11 companies according to the criteria, the observations in this study is 55. Data analysis in this study used panel data multiple regression analysis. The results show that debt to equity has a positive and significant effect on dividend policy in Property and Real Estate Companies. Earning per share has a positive and significant effect on dividend policy in Property and Real Estate Companies.